Advanced Information Systems Engineering 23rd International Conference, CAiSE 2011, London, UK, June 20-24, 2011. Proceedings - Mouratidis, Haralambos; Rolland, Colette (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 23rd International Conference on Advanced Information Systems Engineering, CAiSE 2011, held in London, UK, in June 2011. The 42 revised full papers and 5 revised short papers presented were carefully reviewed and selected from 320 submissions. In addtion the book contains the abstracts of 2 keynote speeches. The contributions are organized in topical sections on requirements; adaptation and evolution; model transformation; conceptual design; domain specific languages; case studies and experiences; mining and matching; business process modelling; validation and quality; and service and management.